Frequent attenders at emergency departments: a linked-data population study of adult patients - Jelinek, G.; Jiwa, Moyez; Gibson, N.; Lynch, A. (Australasian Medical Publishing Company, 2008)
Objectives: To examine the characteristics of adult patient attendances to emergency departments (EDs) in Perth hospitals by patients' frequency of attendance. Design, setting and participants: A linked-data population study of adults (aged = 15 years) attending all nine Perth hospital EDs between 1 July 2000 and 31 December 2006. Main outcome measures: Proportion of frequent attenders (FAs; those attending five or more times annually); and demographic characteristics, mode of arrival at the ED, disposition (admission, transfer, discharge or death), urgency and clinical conditions by frequency of attendance. Results: There was a mean of 1.5 attendances per individual per year, resulting in 1 583 924 attendances by 663 309 individuals over the 6.5 years of the study. Most patients (97.6%) attended Perth EDs fewer than five times a year. The more frequently patients attended, the more likely they were to be male, middle-aged and late-middle-aged, have self-referred, have mental and behavioural disorders and alcohol intoxication, to not wait to be assessed, and to arrive by ambulance. The groups of patients attending between 5-9 and 10-19 times per year (97.4% of FAs) had more urgent conditions, more circulatory system disease and higher admission rates than all other patients. Conclusion: Most FAs at Perth EDs present fewer than 20 times a year and have more serious and urgent illness than other patients, more often requiring inpatient services. A very small minority of patients (around 100 patients/year) attends 20 or more times a year, many with mental and behavioural disorders and alcohol intoxication not requiring hospital admission.